Collecting household level data on varietal diversification and adaptation strategies to climate change in East Africa - Gevel, Jeske M.J, van de; Bijdevaate, M.; Mwenda, P.; Morimoto, Y.; Fadda, Carlo; Bioversity International (2014)
This training manual presents the objectives, tools and approaches used to train a field team for the survey on socio-economic and environmental factors that lead to farmers’ vulnerability as part of a project entitled “Linking genetic vulnerability to loss of resilience to adapt to climate change”. This training manual gives suggestions for field coordinators and researchers who have to train survey teams in field sites on how to collect data from rural households and communities. The methodology was developed and tested in research areas in CCAFS benchmark sites of Nyando and Makueni in Kenya and in Hombolo district in Tanzania.